The qualities of tasks in organic chemistry and diochemistry based on the analysis of entrance procedure at the Faculty of Science, Charles University - Šrámek, Martin; Teplá, Milada (Scientia in educatione, 2023)
This article introduces results of item analysis of chemistry tests used as a part of the admission procedure at the Faculty of Science, Charles University, between 2016 and 2019. This paper focuses on organic chemistry and biochemistry as it follows already published papers focusing on general and inorganic chemistry. The aim of the research was to determine which tasks were the most troublesome for applicants and those with a low discrimination index. The troublesome tasks were found based on the calculation of difficult indexes whereas the item discrimination index was represented by ULI(1/2) and RIR coefficients. The results of the item analysis showed that there are four topics containing troublesome tasks in organic chemistry and biochemistry (reactions in organic chemistry, isomery and constitution of compunds, classification in organic chemistry and enzymes). Additionally, the analysis revealed five topics containing items with a low discrimination index (for example: acidity and basicity of organic compounds, formulae in biochemistry, biochemical reactions, . . . ). Further analysis showed that in many cases, the dicsrimination index of the item decreased with a number of steps necessary for succeeding in the task.